Electrocardiographic P terminal force in lead V1, its components, and the association with stroke and atrial fibrillation or flutter - Wolder, Lecia Dixen; Graff, Claus; Baadsgaard, Kirstine H.; Langgaard, Monica Lykke; Polcwiartek, Christoffer; Ji-Young Lee, Christina; Skov, Morten Wagner; Torp-Pedersen, Christian; Friedman, Daniel J.; Atwater, Brett; Overvad, Thure Filskov; Nielsen, Jonas Bille; et al. (Heart rhythm, 2023)
The electrocardiographic (ECG) marker P terminal force V1 (PTFV1) is generally perceived as a marker of left atrial pathology and has been associated with atrial fibrillation or flutter (AF). The purpose of this study was to determine the association between PTFV1 components (duration and amplitude) and incident AF and stroke/transient ischemic attack (TIA). The study included patients with an ECG recorded at the Copenhagen General Practitioners Laboratory in 2001 to 2011. PTFV1 ≥4 mV·ms was considered abnormal. Patients with abnormal PTFV1 were stratified into tertiles based on duration (PTDV1) and amplitude (PTAV1) values. Cox regressions adjusted for age, sex, and relevant comorbidities were used to investigate associations between abnormal PTFV1 components and AF and stroke/TIA. Of 267,636 patients, 5803 had AF and 18,176 had stroke/TIA (follow-up 6.5 years). Abnormal PTFV1 was present in 44,549 subjects (16.7%) and was associated with an increased risk of AF and stroke/TIA. Among patients with abnormal PTFV1, the highest tertile of PTDV1 (78–97 ms) was associated with the highest risk of AF (hazard ratio [HR] 1.37; 95% confidence interval [CI] 1.23–1.52) and highest risk of stroke/TIA (HR 1.13; 95% CI 1.05 –1.20). For PTAV1, the highest tertile (78–126 μV) conferred the highest risk of AF and stroke/TIA (HR 1.20; 95% CI 1.09–1.32; and HR 1.21; 95% CI 1.14–1.25, respectively). Abnormal PTFV1 was associated with an increased risk of AF and stroke/TIA. Increasing PTDV1 showed a dose–response relationship with the development of AF and stroke/TIA, whereas the association between PTAV1 and AF was less apparent. [Display omitted]